O pojęciu zdarzenia będącego złamaniem prawa przyrody - Kuźniar, Adrian (Filozofia Nauki, 2021)
In this paper, I analyze the concept of an event that breaks a law of nature. My investigations are carried out in the context of David Lewis’s critique of Peter van Inwagen’s Consequence Argument for incompatibilism. It is argued that Lewis’s definition of a “law-breaking event” is too narrow. I offer an amended definition and explore its consequences for the prospects of van Inwagen’s argument.